(untitled) (Global Journals of Research in Engineering, 2023)
In the present research work 30 story building with different type of RC Shear wall at the center in concrete frame structure with fixed support conditions under different type of soil for high seismic zone are analyzed This paper aims to study the effect of seismic load on column forces in different type of RC shear walls in concrete frame structures under different type of soil condition and different load combination Estimation of column forces such as column axial force column moment column shear force column torsion time period and frequency and modal load participation ratios is carried out In dynamic analysis Response Spectrum method is used It was found that the axial force and moment in the column increases when the type of soil changes from hard to medium and medium to soft Since the column moment increase as the soil type changes soil structure interaction must be suitably considered while designing frames for seismic force